CARACTERIZACIÓN MICROBIOLÓGICA DEL MUCÍLAGO DE DOS VARIEDADES DE CACAO NACIONAL Y CCN-51 (Theobroma cacao L) - CABELLO ORMAZA, NARCISA MONSERRATE (2025)
The fermentation of cocoa (Theobroma cacao L.) is a key process in the formation of aromatic compounds, where the mucilage microbiota influences the quality of the fermented bean